Research progress on visual perception system of bionic flapping-wing aerial vehicles - Qiang FU; Xiang-yang CHEN; Zi-liang ZHENG; Qing LI; Wei HE (工程科学学报, 2019)
The bionic flapping-wing aerial vehicle (FWAV) is a kind of aerial vehicle that imitates birds and insects and generates lift and thrust forces using active wing movement. Given its advantages, such as high flight efficiency, strong maneuverability, and good imperceptibility, FWAVs have attracted considerable attention from researchers in recent years. Given its compact structure and easy operation, the small FWAV can adapt itself to complex environments. However, some restrictions are also imposed on its onboard load capacity and battery endurance time. That is, sensors with large weight and high power consumption are no longer suitable for FWAVs in many scenarios. To the best of our knowledge, most of the information obtained by organisms from nature is acquired through vision. As an efficient way to obtain information, vision plays an irreplaceable role in the application of FWAVs. Vision sensors have many advantages, such as light weight, low power consumption, and rich image information. Therefore, these sensors are suitable for FWAVs. With the development of microelectronics and image processing technologies, visual perception systems of the FWAV have also made important progress. First, this study introduces the visual perception system of several representative FWAVs at home and abroad, which can be classified into two categories, i.e., onboard and off-board visual perception systems. Then, this study briefly reviews three key technologies of the visual perception system of FWAVs, namely, image stabilization, object detection and recognition, and object tracking technologies. As a result, research on the visual perception system of FWAVs is still at the initial stage. Finally, this study provides the future research directions of the visual perception system of FWAVs, such as image stabilization, onboard real-time processing, object detection and recognition, and three-dimensional reconstruction.